Alkali-Activated Stabilization of Silt Soil Using Garlic Husk Ash: Mechanical, Microstructural, and Durability Performance - Yılmazoglu, Mehmet Ugur (Elsevier BV, 2025)
This study aims to evaluate the usability of agricultural wastes such as rice husk ash (RHA) and garlic husk ash (GHA) in improving silt soils by the alkali activation method. During the stabilization process, samples prepared with binder systems containing sodium hydroxide (SH) and sodium silicate (SS) at different SH/SS ratios (1, 3, and 9) and additive rates (0%, 4.5%, and 9%) were cured in two different curing environments (cured at ambient temperature—AC and cured in oven at 35 °C—OC) for 7, 28, 56, and 90 days. Mechanical behavior was evaluated by unconfined compressive strength (UCS) and unconsolidated-undrained triaxial compression (UU) tests; environmental strength was analyzed by 25 and 50 cycles of freeze–thaw (F–T) tests. Microstructure development was investigated by SEM and XRD analyses, while sustainability assessment was carried out with carbon footprint (kg·CO2/kg) and carbon efficiency (CI) parameters. The findings showed that mixtures containing 9% RHA and a high SH/SS ratio provided high strength in both AC and OC environments. While using GHA alone provided limited mechanical performance, it increased the binding capacity by creating a synergistic effect when used with RHA. Oven-curing environment increased the speed of pozzolanic reactions and the development of the binder phase, resulting in denser microstructures. In addition, the RHA additive played a critical role in maintaining the resistance against freeze–thaw cycles. Carbon emission analyses revealed that SH and SS had high carbon loads, while RHA and GHA additives provided environmentally sustainable solutions with low carbon footprint and high strength. As a result, alkaline activation systems with RHA and GHA additives offer a strong alternative for sustainable soil improvement applications with high strength and environmental durability.